Translating the 'man-made': an underwater observatory on the shoreline of Lake Malawi - Gruber, Adeline (My University, 2015)
“" at environment and those structures invest the vast di# erences of nature with meaning intelligible to, indeed imagined by, a mankind and they involve in the end all those complex relationships of human buildings with each other that shape within nature a man-made topography.” (Scully 1991: 1) Humankind has forever been placed outside the realm of nature, peering in as a spectator through a frame. ! at which is organic is ‘natural’ and that which we create is ‘man- made’. A beaver’s nest would not exist if the beaver had not built it, yet it is ‘natural’. If humans are of earth then surely that which we build is ‘natural’ as well? Let us translate the ‘man-made’ back into the natural world. Lake Malawi makes up one-third of its country. Local Malawians are dependent on this resource for livelihood, food, water and sanitation but over" shing threatens it. Cichlid " sh native to the lake are a rapidly evolving species, they are also a rapidly depleting food source. ! e lake with its local " shing villages is nature with us in it. I propose an underwater observatory on the shoreline of the lake, to address a species and a food source. Local Malawians inhabit the shoreline within a nature that has been adapted to meet the needs of human activity. Fishermen prepare their nets at sunset, go out at night with # ickering para$ n lamps, and return at sunrise with a diminishing catch of Chambo while women make their way to the water’s edge to wash and collect water. ! e chosen site is situated in Cape Maclear at the entrance to Lake Malawi National Park which is protected aquatic sanctuary. An established tourist industry supports the local community of Chembe village. ! e observatory is a threshold to the park and a liminal boundary between land and water, in and out, above and below. ! e programme is categorized within Science and Community. Communal facilities address alternative food sources, sanitation and education while science facilities document and record the rapid evolution of Cichlids. If architecture can be viewed as a hybrid, a construct of both human culture and nature, then let an amphibious structure rest upon the water’s edge, partially submerged and partially elevated over water and land. Acting as a bathometer, climatic changes mark its surface as it modi" es nature while nature modi" es it. Designed to adapt to # uctuating water levels, the facility evolves as rapidly as its native Cichlid " sh. By reframing the mindset of locals and visitors, we become part of an evolving ecosystem and may begin to truly acknowledge the part we play in it. We attempt to preserve a species and a livelihood, yet preservation may be viewed as the pursuit of stagnation. Our livelihoods, our food and our buildings are of this earth. Like nature, they must continuously adapt, modify and evolve.
This document is submitted in partial ful" lment for the degree: Master of Architecture [Professional] at the University of the Witwatersrand, Johannesburg, South Africa, in the year 2014.
Keywords: Architecture; Environmental aspects; City planning